2007
DOI: 10.1080/01421590701302290
|View full text |Cite
|
Sign up to set email alerts
|

Using an objective structured clinical examination (OSCE) to assess multiple physician competencies in postgraduate training

Abstract: The OSCE may be useful as a reliable and valid method of simultaneously assessing multiple physician competencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
61
0
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 19 publications
2
61
0
7
Order By: Relevance
“…It has been viewed as the cornerstone of health care professional assessment for a number of years as it provides a standardised approach to assessment (Byrne and Smyth, 2008;Rushforth, 2007;Jefferies et al, 2007). However there are a number of limitations to this form of assessment for non-medical prescribing students.…”
Section: Osce and 'Live' Practice Based Assessmentmentioning
confidence: 99%
“…It has been viewed as the cornerstone of health care professional assessment for a number of years as it provides a standardised approach to assessment (Byrne and Smyth, 2008;Rushforth, 2007;Jefferies et al, 2007). However there are a number of limitations to this form of assessment for non-medical prescribing students.…”
Section: Osce and 'Live' Practice Based Assessmentmentioning
confidence: 99%
“…Much excellent work has been accomplished in this field in other domains of medical education. 15,16 Surgical residents are rarely observed or evaluated when they are doing histories and physical examinations, talking to patients about ethical issues, or discussing the risks and gains of surgical treatment. It is unusual for a senior surgeon to observe a resident in any interaction with patients other than performing operations or procedures.…”
Section: Commentsmentioning
confidence: 99%
“…23,24 An OSCE has also been used to assess multiple CanMEDS competencies in other fields of postgraduate training, such as radiology and neonatology. 6,25 To our knowledge, no research exists regarding methods of assessing the intrinsic roles in orthopedic postgraduate training. We hypothesized that an OSCE designed to assess multiple intrinsic CanMEDS roles would have sufficient reliability and validity to distinguish between different years of postgraduate training in orthopedic residents.…”
mentioning
confidence: 99%
“…4 A survey of a wide variety of medical and surgical program directors in Canada identified that the ITER is the most commonly used method to evaluate the CanMEDS roles, despite its acknowledged subjective nature. [5][6][7] Respondents reported dissatisfaction with current methods of evaluating the intrinsic roles, especially the manager and health advocate roles.…”
mentioning
confidence: 99%